2012
DOI: 10.3329/icpj.v1i5.10281
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of RP-HPLC method for determination of Duloxetine hydrochloride in bulk and dosage form

Abstract: A reverse phase high performance liquid chromatographic method was developed for the determination of duloxetine hydrochloride in bulk and dosage form. The separation was effected on a kromasil ODS C18 column (250mmX4.6mm, 5?) using a mobile phase mixture of buffer and methanol in a ratio of 85:15 v/v at a flow rate of 1.0ml/min. The detection was made at 230nm. The retention time of duloxetine hydrochloride was found to be 3.443±0.06 min. Calibration curve was linear over the concentration range of 20-120?g/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Samples were withdrawn at appropriate times and analysed by HPLC after suitable dilution [7,[24][25][26][27]. Peak purity and mass balance were monitored for each degradation condition.…”
Section: Timementioning
confidence: 99%
See 1 more Smart Citation
“…Samples were withdrawn at appropriate times and analysed by HPLC after suitable dilution [7,[24][25][26][27]. Peak purity and mass balance were monitored for each degradation condition.…”
Section: Timementioning
confidence: 99%
“…Various analytical methods have been reported namely, HPLC [10][11][12][13][14][15][16][17], high-performance thin-layer chromatography [18,19], ultra-performance liquid chromatography [20] and liquid chromatography-tandem mass spectrometry [21][22][23]. Degradation studies have also been reported [24][25][26][27] under thermal, acidic, alkaline, neutral hydrolysis and oxidative photolytic stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Mirabegron binds with beta-3 adrenoreceptors and has been shown to decrease the muscle contractions. A thorough literature search revealed that RP-HPLC method for pharmaceutical dosage form, 6 GC method for residual solvent analysis 7 and one bioanalytical method has been reported for the determination of MIR in the human plasma by LC-MS/MS for clinical pharmacokinetic study. 8 To the best of our information, a comprehensive stress degradation study has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, several analytical research approaches have been reported for assaying of MIR in biological fluids, synthetic matrices, or pharmaceutical dosages. Examples of such analytical methods included HPLC, 13 RP-HPLC, [14][15][16][17] UPLC, 18,19 UHPLC, 20 LC-MS, and LC-MS/MS, [21][22][23] HPTLC, 24 and TLC plates. 25 Nevertheless, UV spectrophotometric [26][27][28][29] and spectrofluorimetric methods 30 were also reported.…”
mentioning
confidence: 99%